Proteasome caspase-like activity regulates stress granules and proteasome condensates - Steinberger, Shirel; Adler, Julia; Myers, Nadav; Shaul, Yosef (Frontiers in Cell and Developmental Biology, 2025)
The 20S proteasome maintains cellular protein homeostasis, particularly during stress responses. In a previous study, we identified numerous 20S proteasome substrates through mass spectrometry analysis of peptides generated from cellular extracts degraded by purified 20S proteasome. Many substrates were found to be components of liquid-phase separation, such as stress granules (SGs). Here, we demonstrate the degradation products arise from the caspase-like (CL) proteasomal activity. To investigate the functional implications of CL activity, we generated cell lines devoid of CL function by introducing the PSMB6 T35A mutation. These mutant cells exhibited slower growth rates, heightened sensitivity to stress, and activation of the unfolded protein response (UPR), as indicated by elevated levels of spliced XBP1 (sXBP1) and stress markers. Cells were subjected to arsenite and osmotic stress to assess their responses. Our findings reveal that CL activity is crucial for efficient SG assembly but does not significantly affect SG clearance. Interestingly, in these mutant cells, proteasomes were more cytoplasmic under normal conditions but formed nuclear condensates/granules (PGs) upon NaCl osmotic stress. However, the PGs were unstable and rapidly dispersed. These findings underscore the important role of the proteasome’s CL activity in managing stress-induced dynamics of liquid-liquid phase, highlighting its importance in cellular adaptation to proteotoxic and genotoxic stress conditions.